Bricolage, spreco ed economia della festa - Laura Bonato (EtnoAntropologia)
The issue of ceremony can be analyzed in terms of  “cultural bricolage”: it consists of using different pieces made free by shattering and recombining them in a broader conceptual arena. Ceremonies, in fact, involve both tradition, parts of different rituals, and collective representations. In doing this, they succeed in their aim: identify new meanings which fit perfectly with contemporary lifestyles. Cultural bricolage, however, can also be investigated in terms of game and fun: in this respect two particular ceremonies will be analyzed: the battle of the oranges, characterizing the Historical Carnival of Ivrea, and the Tomatina of Buñol. The common point between the two ceremonies is waste. As we will see, waste is functional to the success of the ceremonies themselves, as they feature an exaggerated use of food, respectively oranges and tomatoes which are thrown to the public during the “battles”, in a sort of ritualized aggression.